2013
DOI: 10.2478/10004-1254-64-2013-2184
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Histological Changes in Rat Liver Caused by Cypermethrin and Beta-Cyfluthrin

Abstract: Cypermethrin and beta-cyfl uthrin are two most widely used multipurpose pyrethroids. After determining their oral LD 50 (416.98 mg kg -1 and 354.8 mg kg -1 body weight, respectively), we assessed their hepatotoxicity in Wistar rats following acute (0.1 LD 50 for 1 day) and sub-acute (0.1 LD 50 for 7, 14, 21 or 28 days) poisoning. The assessment was based on hepatic marker enzymes AST, ALT, LDH, ALP, glycogen, total proteins, total lipids, cholesterol, free fatty acids, and phospholipids. AST, ALT, LDH, total l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 27 publications
6
34
0
Order By: Relevance
“…Cypermethrin was also report to induce the level of MDA with a concomitant increase in ROS [19] . The increased level of MDA observed in ECM inhalation was also reported as a result of pyrethroid insecticides exposure by several authors [20][21][22][23][24] . The current value of SOD activity represent a significant decrease in ECM-intoxicated groups (p≤0.001).…”
Section: Discussionsupporting
confidence: 63%
“…Cypermethrin was also report to induce the level of MDA with a concomitant increase in ROS [19] . The increased level of MDA observed in ECM inhalation was also reported as a result of pyrethroid insecticides exposure by several authors [20][21][22][23][24] . The current value of SOD activity represent a significant decrease in ECM-intoxicated groups (p≤0.001).…”
Section: Discussionsupporting
confidence: 63%
“…Disturbed liver homeostasis under such stress is sufficient to alter normal body physiology of any organism. Liver is a hub for protein synthesis, regulating cell functions such as maintenance of cellular rigidity, flow management of material through cell membranes, catalysis of an extraordinary range of chemical reactions, regulation of metabolic concentration, and arrangement of nuclear material to control gene function (Bhushan et al, 2013). Histological observations were recorded in liver of all the rats collected from PAU and Bathinda region.…”
Section: Fig 1 Relative Weight Of Vital Organs (G/100 G Bw) In Diffmentioning
confidence: 99%
“…The hepatocytes appeared vacuolated ballooned and some of them showed degenerative changes while the nuclei appeared pyknotic and densely stained in rats. Histopathological examination of the liver from animals treated with cypermethrin and beta-cyfluthrin also revealed various cellular and lobular abnormalities, including intralobular vein (ILV) membrane dilation, presence of hepatocytes in ILV, cytoplasmic vacuolisation, multinuclear cells, nuclear polymorphisms, nuclear vacuolisation, hepatocyte membrane damage, nuclear division, nuclear eccentricity, pyknosis, necrosis, and karyorrhexis (Bhushan et al, 2013). Heikal et al (2013) reported histopathological alterations in liver of cyromazine and chlorpyrifos treated rats which include degeneration and coagulative necrosis in the hepatocytes, inflammatory cells infiltration, and kupffer cells proliferation.…”
Section: Fig D Light Micrograph Of a Ts Of Kidney Of Tindica Femmentioning
confidence: 99%
“…There is extensive contact to many pesticide, affected liver and kidneys, [6] there is also a raise in the occurrence of liver disorders among Ranch Hand workers in large contact category [7]. If we statistically analyzed then there is comparatively high level of aspartate aminotransferase (AST) were found in agriculture workers who are constantly exposed to pesticides [8].…”
Section: Introductionmentioning
confidence: 99%
“…Most of industrial workers who are steadily exposed to pesticides the elevated levels of gamma glutamyl transferase (GGT) were found in the blood of [8,9]. It has also been observed that high amount of liver dysfunction was observed with elevated (AST), alanine aminotransferase (ALT), or lactate dehydrogenase (LDH) [7][8][9][10][11]. Studies revealed that AST and ALT produces their effects on the process of breakdown of amino acids into α-keto acid which are in flight for complete metabolism through the Kreb's cycle and electron transport chain.…”
Section: Introductionmentioning
confidence: 99%